Evidence that the Appressorial Development in Barley Powdery Mildew is Controlled by MAP Kinase Activity in Conjunction with the cAMP Pathway - Kinane, J.; Oliver, Richard (2003)
Development of the barley powdery mildew fungus involves the sequential formation of a primary germ tube, an appressorial germ tube, and an appressorium. Previously, we have shown that the cAMP pathway controls the emergence of the two germ tubes. Following identification of two MAP kinase genes in an EST database from developing conidia we studied the role of the MAP kinase pathway and its interaction with the cAMP pathway. Fungal MAP kinase activity increased rapidly during mildew development, reaching a maximum between 2 and 8 h after inoculation. Sphingosine or PAF-16, activators of the MAP kinase pathway, increased activity and appressorial development whilst an inhibitor, PD 98059, decreased both. Studies on the interaction between the cAMP and MAPK pathways revealed that several effectors of the MAPK pathway had no effect on cAMP levels. However upstream effectors of the cAMP pathway, such as cholera toxin and pertussis toxin (activators of Gα proteins) increased MAPK activities whereas downstream effectors such as forskolin (adenylyl cyclase activator) or H89 (PKA inhibitor) had no effect. Combined application of forskolin and sphingosine produced a rise in appressorial germ tube and appressorial formation higher than when either pathway was stimulated individually. These results suggest that the two pathways cooperate in appressorial development.